- TINDAK PIDANA MENYEBARKAN BERITA BOHONG MERUGIKAN KONSUMEN DALAM TRANSAKSI ELEKTRONIK SECARA BERSAMA-SAMA: - - Muhammad Daffa Zacky Parnanda; Vience Ratna Multiwijaya (Reformasi Hukum Trisakti, 2023)
By setting up fake virtual accounts using a BCA account in the name of Michael Lisardo, the defendant allowed Sunandar to send fictitious bills to consumers where the defendant worked on behalf of Michael Lisardo and Sunandar, who were fired from an online lending company. The funds are then utilised for individual advantage. The issue's description is as follows: Does the defendant's behavior fall within the parameters of Article 28 Paragraph (1) and Article 45 Paragraph (2) of Law No. 19 of 2016, which amended Law No. 11 of 2008, and how those who commit TP crimes spread false and misleading information during electronic transactions at the expense of all consumers? Two types of data are used in the research method: primary and secondary employing inductive reasoning and qualitative methods. The findings of the investigation and discussions revealed that the defendant's activities did not comport with the judgment that had been rendered against him. The study's findings suggest that since the punishment  that was imposed not proper for the defendant's conduct, investigators should exercise greater caution when determining the defendant's punishments. This will help establish the principle of legal certainty and allow the defendant to pursue legal remedies.